Additive and subtractive manufacturing of layered titanium-matrix composites: interface behaviour and forming mechanisms - Rui Wang; Dongdong Gu; Hao Ye; Kaijie Lin; Han Zhang (Virtual and Physical Prototyping)
To prepare the titanium-matrix composites (TMCs) reinforced by high-content ceramic, multi-material laser powder bed fusion (LPBF) technology was utilised to process layered TMCs. The relationship between the processing parameters, forming quality, interface behaviour, and machinability of multi-material LPBF-processed layered TMCs was clarified based on an additive and subtractive manufacturing route. By collaboratively adjusting the processing parameters of the titanium alloy layer and composite layer, high-density samples without interfacial defects were successfully obtained. High laser power was found to enhance the interfacial element diffusion and promote a gradient transition in ceramic whisker concentration. The hard TiB whiskers’ hardening effect and fine-grain strengthening effect realised the synergistic improvement of hardness and strength. Moreover, the interfacial microstructure and cutting mechanism of layered TMCs were revealed. The masking phenomenon induced by the thermal softening effect was stronger than the pull-out phenomenon of whiskers, which reduced the surface roughness and improved the cutting surface flatness of multi-material LPBF-processed layered TMCs.